2020
DOI: 10.1186/s13018-020-01659-w
|View full text |Cite
|
Sign up to set email alerts
|

A novel anatomically pre-contoured side-specific titanium plate versus the reconstruction plate for quadrilateral plate fractures of the acetabulum: a propensity-matched cohort study

Abstract: Background Surgical treatment of acetabular fractures involving a quadrilateral plate is a challenge to orthopedic surgeons. We have developed a novel fixation technique using a specially shaped reconstruction plate combined with several buttress screws of a quadrilateral plate which was also called a dynamic anterior plate-screw system for quadrilateral plate (DAPSQ) to treat acetabular fractures involving quadrilateral plate since 2005 (RP group). And the long-term follow-up results have confirmed the effect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Therefore, the maintained reduction and buttress provided by internal fixation to the quadrilateral region are essential. Recently, many newly designed prebent suprapectineal or infrapectineal plates have been proposed to buttress the quadrilateral area which was known as a thin cortical region [ 11 15 ]. Furthermore, He found and reported that there was a “safe zone” for infrapectineal plate fixation for quadrilateral surfaces, but he did not mention the effect of screw purchase and fixation construct buttress for the thin part of the quadrilateral surface [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the maintained reduction and buttress provided by internal fixation to the quadrilateral region are essential. Recently, many newly designed prebent suprapectineal or infrapectineal plates have been proposed to buttress the quadrilateral area which was known as a thin cortical region [ 11 15 ]. Furthermore, He found and reported that there was a “safe zone” for infrapectineal plate fixation for quadrilateral surfaces, but he did not mention the effect of screw purchase and fixation construct buttress for the thin part of the quadrilateral surface [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, in this study, although the postoperative imaging evaluation of acetabular plate fracture was analyzed in depth, it should be further discussed whether there is a closer relationship between the postoperative imaging evaluation of acetabular plate fracture and patients’ functional outcomes. In our experience, achieving good functional results after acetabular fracture not only lies in the anatomical repositioning of the acetabulum, but also requires patients to adhere to a reasonable rehabilitation after surgery [ 22 ]. Thirdly, in spite of the simplifications in the measurement of these three angles, the measurement steps are still complex, which may hinder clinical promotion and popularization.…”
Section: Limitationsmentioning
confidence: 99%
“…Additionally, it could successfully lower the length of the incision, the amount of blood lost during surgery, and the duration of the procedure. For the clinical management of complicated pelvic and acetabular fractures, it could be a preferable option [21] . More studies are required to compare the results as there are a lot of controversies about the indications and safety of the pararectus approach.…”
Section: Discussionmentioning
confidence: 99%